1984
DOI: 10.1136/jcp.37.10.1101
|View full text |Cite
|
Sign up to set email alerts
|

Histological appearances of intracranial biopsies obtained using the Cavitron ultrasonic surgical aspirator.

Abstract: The Cavitron ultrasonic surgical aspirator causes localised ultrasonic tissue fragmentation and has recently been used to remove intracranial tumours. We have examined tissue fragments from 17 operations in which the apparatus was used: in all cases a definitive diagnosis could be made from the material aspirated. This finding has not been previously described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…16,17 Typically, aerosolized tum our cells are dispersed within an environment, which has been supporting their grow th. W hile aerosolization may result in morphologic changes, which affect their long-term viability, 18,19 our observations as well as previous reports point to potential viability of these cells. 6,7 …”
Section: Discussionsupporting
confidence: 82%
“…16,17 Typically, aerosolized tum our cells are dispersed within an environment, which has been supporting their grow th. W hile aerosolization may result in morphologic changes, which affect their long-term viability, 18,19 our observations as well as previous reports point to potential viability of these cells. 6,7 …”
Section: Discussionsupporting
confidence: 82%
“…As one of the first research groups, Malhotra et al [1] investigated whether ultrasonically aspirated tissue can be used for histopathological studies, and they found positive results for all resected tumors. Similar observations have been made by Blackie and Gordon [2], who investigated tumor tissue fragments from 17 resections and were able to give the correct diagnosis for all aspirated samples. Furthermore, Oakes et al [3] could establish cell cultures from CUSA material of patients with medulloblastoma.…”
Section: Introductionsupporting
confidence: 66%
“…CUSA EXcel) might consistently have a greater amount of vital tumor cells than tissue obtained by standard biopsy methods, especially glioma tissue; furthermore, it is much more easily retrieved from the suction trap than from a sterile disposable sack within the system. Thus, the utilization of material from the suction trap may facilitate pathological interpretation [2] by providing a more representative sample of tumor histology as well as an adequate, sterile and convenient source of tumor material for further cellular or molecular studies [7]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been three previous reports describing the histopathology of CNS tumors removed with the CUSA. [5][6][7] We recently evaluated the cytomorphologic appearance of 22 CNS tumors obtained by the CUSA and analyzed which types of the neoplasms showed the best preser~ation.~ The study reported in the present article investigated the immunocytochemical staining patterns of the material obtained with the CUSA, which in some cases was the only biopsy material available. Knowledge of the reliability of immunocytochemical reactions on CUSA material from a given tumor is of considerable importance to the surgical pathologist and cytologist, so presented herein are the results of immunocytochemical reactions for 11 cases of meningioma, three cases of glioblastoma multiforme, one astrocytoma, and two schwannomas.…”
mentioning
confidence: 99%